COMMERCIAL AND SEED RESOURCES OF TARGET MARINE SPECIES IN NHA TRANG BAY - Long, Nguyen Van; Quang, Thai Minh; Dat, Mai Xuan (Vietnam Journal of Marine Science and Technology, 2016)
Assessments of commercial and seed resources of target marine species exploited in Nha Trang bay were conducted in 2014 - 2015 through 8 consultations with 8 local communes/wards surrounding the bay in combination with 4 field surveys (December 2014; May, August and September 2015) to assess locations of important spawning and nursery grounds of target resources. Results from this study showed that there were 25 target resources of abalones, lambis and turbo snails, top shells, strawberry conch, scallops, squids and cuttlefish, swimming crab, spiny lobsters, sea cucumbers, rabbitfishes, anchovies, breams, scads and ponyfishes with an annual commercial catch and revenue of 651.3 tonnes and 65 billion VND respectively in 2014. The reef related resources contributed similar catch and higher revenue (323.9 tons and 21.56 billion VND) than the reef resources (327.4 tons and 11.11 billion VND), in which rabbitfish was the most important group. In addition, harvesting of seeds of spiny lobsters for marine aquaculture was also important activity to fishery in the bay, giving a total catch and revenue of 212.000 seeds and 32.34 billion VND per year and this revenue was 3 times higher than that of the commercial resources directly harvested from the reefs. The Sargassum beds and coral reefs in the bay were important spawning and nursery grounds for squids, abalones, turbo snails, top shells, spiny lobsters and rabbitfishes.